Cryptococcal Meningitis: A Retrospective Cohort of a Brazilian Reference Hospital in the Post-HAART Era of Universal Access - Aline Z. de Azambuja; Gustavo Wissmann Neto; Guilherme Watte; Luciana Antoniolli; Luciano Z. Goldani (Canadian Journal of Infectious Diseases and Medical Microbiology)
Objective. Cryptococcus neoformans is a common opportunistic infection in adults with acquired immunodeficiency syndrome worldwide. However, limited data exist for HIV-infected patients in the post-HAART (highly active antiretroviral therapy) era in Brazil. The aim of this study was to describe the clinical characteristics and outcomes of cryptococcosis in a cohort of patients attending a teaching tertiary care hospital in southern Brazil after the introduction of HAART in Brazil. Patients and Methods. A retrospective study was conducted in tertiary care hospital in southern Brazil. Detailed data on risk factors, clinical manifestations, diagnosis methods, treatment, and prognosis of patients with meningeal cryptococcosis were evaluated from January 2009 to December 2016. Results. Seventy-nine cases of cryptococcal meningitis were identified. Most of the patients presented positive CSF (cerebrospinal fluid) cultures for Cryptococcus neoformans (96%). The prevalence of males and females with meningeal cryptococcosis was similar. The age of the patients ranged from 5 to 67 years. The median time of hospitalization was 28 days. The most common underlying disease was HIV (82%), followed by solid transplant (10%). Fever, nausea, vomiting, headache, and altered mental status were the most common clinical manifestations. Initial opening intracranial pressures varied from 30 to 130 cm H2O. CNS imaging abnormalities include hydrocephalus and hypodensities. Widened Virchow–Robin spaces were described in only 2 patients (2.5%). Induction treatment of the majority of the patients consisted of amphotericin B and flucytosine (67%) followed by amphotericin B and fluconazole (19%). Multivariate analysis of Cox regression identified headache at presentation, mechanical ventilation, CSF glucose <20 mg/dL, and CSF cryptococcal antigen ≥1 : 1000 for independent risk factors for death. All-cause 30-day and 60-day mortalities were 19% and 24%, respectively. Conclusions. Meningeal cryptococcosis mostly caused by C. neoformans continues to occur predominantly in HIV-infected adults despite HAART being widely distributed in Brazil. Cryptococcosis remains a significant opportunistic infection in solid organ transplant recipients. Despite adequate antifungal treatment and management of intracranial hypertension in a reference tertiary care hospital, mortality was high. Identification of risk factors and additional treatment modalities, especially for intracranial hypertension, are necessary to improve care for patients with cryptococcal meningitis.